HUBUNGAN BUDAYA ORGANISASI DENGAN PRESTASI KERJA KARYAWAN PADA PERUM BULOG DIVISI REGIONAL DI YOGYAKARTA - Kismantoroadji, Teguh; Arumsari, Vini; Nurhayati, Rina (Jurnal Dinamika Sosial Ekonomi, 2009)
The relationship between Culture Organization with Employees Achievement at Division Regional of Perum Bulog in Yogyakarta. This research purposed of knowing culture organization, employees achievement at Division Regional of Perum Bulog in Yogyakarta and to knowing about relationship both of them. The basic method used was descriptive method and the research method was survey method. The method to take the respondents was non probability sampling method. The types of data used were primary data and secondary data. The source of thye data were gained from Division Regional of Perum Bulog in Yogyakarta of Human Resource division, library study and internet. The data were colected through interview and questioner. The finding showed that the culture organization is very high, employees achievement is very good and both of them have a positf relationship.Keywords: culture organization, employees achievement